VD_FINDINFO HC / 2015 / 861 vom 4. August 2015 - VD Tribunal cantonal (2015)
SÛRETÉS, JUGE ARBITRE, ACTION EN NOMINATION, DÉPENS, CONSTATATION DES FAITS | 107 al. 1 let. e CPC (CH), 320 CPC (CH), 99 al. 3 let. c CPC (CH), 6 TDC